Examining pediatric cases from the clinical research office of the endourological society ureteroscopy global study - Güven, Selçuk; Basiri, Abbas; Varshney, Anıl Kumar; Arıdoğan, İbrahim Atilla; Miura, Hiroyasu; White, Mark; Kılınç, Mehmet; de la Rosette, Jean J. M. C. H. (Elsevier Science Inc, 2017)
OBJECTIVE To evaluate the characteristics and outcomes of ureteroscopy (URS) in children treated in several hospitals participating in the Clinical Research Office of the Endourological Society (CROES) Study, and to present the overall results of pediatric URS compared with adults. PATIENTS AND METHODS The CROES Study collected data on consecutive patients treated with URS for urolithiasis at each participating center over a 1-year period. The collected prospective global database includes data for 11,885 patients who received URS at 114 centers in 32 countries. Of these URStreated patients, 192 were <= 18 years old. RESULTS Of the 114 centers participating in the study, 42% had conducted pediatric URS. Among the pediatric cases, 7 were infants, 53 were small children, 59 were school-aged children, and 73 were adolescents. A considerable number (37%) of the pediatric cases had previously undergone URS treatment. No differences in the surgical outcomes of the adults and children were reported. The URS-treated children had a greater number of positive preoperative urine cultures when compared with adult cases treated. A semirigid scope was used in the vast majority of pediatric cases (85%). According to the present data, within the group of URS-treated children, the younger the child, the more readmissions occurred. CONCLUSION URS is as efficient and safe in children as it is in adults. The data suggest that readmissions among URS-treated children are associated with age, with the likelihood of readmissions greater among younger age groups.
WOS: 000398958100012
PubMed ID: 27888151
Keywords: Pediatric Cases; Clinical Research Office; Endourological Society Ureteroscopy Global Study